Strategi Pengembangan Badan Usaha Milik Desa Surya Sejahtera - Riezka Arum Sulistyawati; Ananta Prathama (SOCIETAS, 2023)
BUMDes Surya Sejahtera is a BUMDes that is in the village of Kedungturi, Taman, Sidoarjo. BUMDes Surya Sejahtera has 4 enterprise units namely UED – SP, Unit of Trade, TPST (Place for Integrated Waste Disposal), and Unit of Partnership Enterprise. BUMDes Surya Sejahtera is a role model for other BUMDes in the Sidoarjo district as well as the first MoU unit of minimarket and sewing partnership in the district. The aim of this researcher is to know the development strategy used by BUMDes Solar Welfare. The research uses qualitative research methods with data collection techniques such as observations, interviews, and documentation. Data analysis techniques are carried out through data collection, data condensation, data presentation, and conclusion drawing. The results of the research show that the development strategy carried out by BUMDes Solar Safety has been done quite well and in accordance with the existing theory, but it is also necessary to make further improvements and development strategies in terms of the development of the marketing network. Need for further development related to marketing development need for new innovations related to how sales such as starting to sell goods or products from trade stores online through social media specialized products BUMDes or E-Commerce in order to the goal of BUMdes development strategy that is increasingly advanced and continues to innovate.